Komparasi Metode Kalkulasi Nilai Tambah Pada Laporan Keuangan PT. Mayora Indah Tbk. - Arief Nurdiannova Qurochma (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2019)
This research aims to observe the value added economically, financially, and based on market towards financial statements of PT. Mayora Indah Tbk. This research uses quantitative method by using available formulas related to the Economic Value Added (EVA), Financial Value Added (FVA), and Market Value Added (MVA). Based on the three kinds of value added calculation in six years from 2013 to 2017, it can be summarized that the company was generally in a good condition. It can be proven from the result of EVA that the value of the 2014 to 2018 was in positive result (lebih dari 0) than that of the 2013. The positive result is also appeared on the FVA and MVA remark from 2013 to 2018.